The information system stress, informatics competence and well-being of newly graduated and experienced nurses: a cross-sectional study - Anu-Marja Kaihlanen; Kia Gluschkoff; Elina Laukka; Tarja Heponiemi (BMC, 2021)
Abstract Background The use of information systems takes up a significant amount of nurses' daily working time. Increased use of the systems requires nurses to have adequate competence in nursing informatics and is known to be a potential source of stress. However, little is known about the role of nursing informatics competence and stress related to information systems (SRIS) in the well-being of nurses. Moreover, the potential impact of nurses' career stage on this matter is unknown. This study examined whether SRIS and nursing informatics competence are associated with stress and psychological distress in newly graduated nurses (NGNs) and experienced nurses. Methods A cross-sectional study was conducted in Finland between October and December 2018. The participants were NGNs (n = 712) with less than two years of work experience and experienced nurses (n = 1226) with more than two years of work experience. The associations of nursing informatics and SRIS with nurses' stress and psychological distress were analyzed with linear regression analysis. Analyses were conducted separately for NGNs and experienced nurses. Models were adjusted for age, gender, and work environment. Results SRIS was associated with stress / psychological distress for both NGNs (β = 0.26 p < 0.001 / β = 0.22 p < 0.001) and experienced nurses (β = 0.21 p < 0.001/ β = 0.12 p < 0.001). Higher nursing informatics competence was associated with lower stress (β = 0.20 p < 0.001) and psychological distress (β = 0.16 p < 0.001) in NGNs, but not among experienced nurses. Conclusions SRIS appears to be an equal source of stress and distress for nurses who are starting their careers and for more experienced nurses, who are also likely to be more experienced users of information systems. However, informatics competence played a more important role among NGNs and a lack of adequate competence seems to add to the strain that is already known to be high in the early stages of a career. It would be important for educational institutions to invest in nursing informatics so that new nurses entering the workforce have sufficient skills to work in increasingly digital health care.